Penerapan Media Kartu Domino Ekonomi (DOKON) untuk Meningkatkan Keaktifan Belajar Siswa pada Materi Sistem Pembayaran - Muhammad Fahmi Bachrul Aditya; Putra Hilmi Prayitno (Lembaga Yasin AlSys, 2026)
Low student learning activity in Economics subjects is often related to the delivery of conceptual material that is theoretical and monotonous, including the Payment System material. This study aims to improve the learning activity of class X-K students at SMA Negeri 1 Pandaan through the application of the innovative Economic Domino Cards (DOKON) media. This study used the Classroom Action Research (CAR) method, which was conducted in one action cycle involving 23 students as respondents. Data on learning activity were collected through direct observation sheets by observers, while the practicality level of the media was measured using a student response questionnaire. The results showed that the application of DOKON media was able to increase student participation in learning, as indicated by an average classical learning activity score of 87.50% in the very high category. In addition, DOKON media received very positive responses from students, with an average practicality percentage of 86.33%. These findings affirm that game-based learning through the use of physical manipulative objects can create a more active, collaborative, and student-centered learning atmosphere. The conclusion of this study shows that Economic Domino Cards media are feasible for use as an alternative innovative learning medium to improve students’ learning activity in the Payment System material. The implications of this study provide practical contributions for Economics teachers in designing more interactive, enjoyable, and meaningful learning.